The Non Linear Finite Element Model for Characterization of Brick Masonry Infill Wall under Cyclic Lateral Forces - B. Budiono; Herwani Herwani (Journal of Mathematical and Fundamental Sciences, 2003)
Brick masonries as the infill walls between columns, for some degree of horizontal loading, are capable of resisting the horizontal load as shear walls. The different behavior of the structure due to the existence of the brick masonries in this case will change the stiffness as well as the strength of the structure. Ignoring this contribution of the brick masonries develops a misleading concept and design for the structure. In this study, a mathematical model representing the relationship between uniaxial stress vs. strain and the failure envelope of the infill brick wall masonry is developed. The implementation of the model is expected to be capable for analyzing the behavior of the structures subjected to external load in particular under cyclic loading. The model assumes that the contribution of the infill walls are taken into account for the analysis and the brick material used is considered as a compression dominated material. Analysis was carried out using non-linear discrete finite element method. Eight nodal isoparametric elements are developed representing concrete and brick masonry elements. Steel reinforcement and linkage elements are modeled as three nodal plane truss element. The variables studied in the analysis are degree of energy dissipation and stiffness degradation. The result showed that the model gives satisfactory results. However, some improvement needs to be considered in the linkage element model.